Study on operation management of borehole heat exchangers for a large-scale hybrid ground source heat pump system in China. (15th March 2017) - Luo, Jin; Zhao, Haifeng; Jia, Jia; Xiang, Wei; Rohn, Joachim; Blum, Philipp
Abstract: For large-scale Ground Source Heat Pump (GSHP) systems, the numerous Borehole Heat Exchangers (BHEs) are generally managed in units. The simultaneous operation of BHEs consume huge amount of energy by operating water-circulating-pumps. However, such an operation condition may waste energy when no peak thermal load is needed. Hence, operation management should be optimized according to timely energy demand to ensure efficient performance with minimum maintenance. In this paper, three operation conditions for a cooling load dominated GSHP system in China are studied. First, specific ground conditions of the BHE field are investigated. The GSHP system operation under intermittent heating and cooling conditions is simulated by Thermal Performance Test (TPT). In order to examine performance of the BHEs and ground temperature migration, a numerical heat transport model is developed. Modeling results indicate similar thermal performance of BHEs and ground temperature disturbance among the three operation alternatives over a 25-year period. Finally, economic performance and operating savings are analyzed. The optimized operation condition in which the operating numbers of BHEs was designed with monthly energy demand of the building could save around 25, 000 CNY (∼3000 EUR) annually. Highlights: TPTs are conducted to simulate BHEs operating for heating and cooling scenarios. A numerical mode is developed to study heat transport of the BHEs. Thermal efficiency of the BHEs and ground temperature migration is analyzed. Operating costs can be saved in the optimized operating strategy.